Mum's robot - Atkins, Jill; Leftheri, Eleftheria-Garyfallia (Wayland London, 2010)
Mad Uncle Albert loves making machines and inventions for his family, but they don't always turn out as they should. Luckily Uncle Albert manages to save the day